Isolation of copper and streptomycin resistant phytopathogenic Pseudomonas syringae from lakes and rivers in the central North Island of New Zealand - Vanneste, J.L.; Cornish, D.A.; Yu, J.; Boyd, R.J.; Morris, C.E. (New Zealand Plant Protection, 2008)
Plant pathogenic strains of Pseudomonas syringae were isolated from lakes and rivers in the central North Island of New Zealand These strains were identified by their ability to produce a fluorescent pigment on a modified Kings B medium by their ability to cause a hypersensitive reaction when infiltrated into tobacco plant and by the absence of a cytochrome c oxidase Different aspects of the protocol used to isolate these strains have been assessed Some of the strains isolated and in some cases the majority of them were resistant to copper and/or streptomycin Significantly these plant pathogenic bacteria were isolated from waterways in areas where no agriculture or horticulture is present and waterways used for crop irrigation These results suggest that natural waterways could be a source of inoculum of plant pathogenic bacteria and a source of genes that confer streptomycin resistance and/or copper resistance to these bacteria